2016
DOI: 10.7314/apjcp.2015.16.18.8079
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Metformin Use for Cholangiocarcinoma

Abstract: Metformin is an oral anti-hyperglycemic agent, which is the most commonly prescribed medication in the treatment of type-2 diabetes mellitus. It is purportedly associated with a reduced risk for various cancers, mainly exerting anti-proliferation effects on various human cancer cell types, such as pancreas, prostate, breast, stomach and liver. This mini-review highlights the risk and benefit of metformin used for cholangiocarcinoma (CCA) prevention and therapy. The results indicated metformin might be a quite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Although metformin provided the most effective prevention on BTC, it might not be a useful therapeutic agent because its use was not associated with a better prognosis among incident cases of BTC (Figure 3). This is compatible with most previous studies that consistently showed a null effect when metformin was used for the treatment of BTC (10)(11)(12). Because BTC is highly malignant (1,2), the more remarkable effect of metformin on the prevention of BTC renders a chance to reduce a greater burden of this life-threatening cancer if metformin is used for early prevention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although metformin provided the most effective prevention on BTC, it might not be a useful therapeutic agent because its use was not associated with a better prognosis among incident cases of BTC (Figure 3). This is compatible with most previous studies that consistently showed a null effect when metformin was used for the treatment of BTC (10)(11)(12). Because BTC is highly malignant (1,2), the more remarkable effect of metformin on the prevention of BTC renders a chance to reduce a greater burden of this life-threatening cancer if metformin is used for early prevention.…”
Section: Discussionsupporting
confidence: 90%
“…Because of the highly malignant nature of BTC, metformin does not provide a useful therapeutic benefit or improve the survival of the patients once BTC is diagnosed (10)(11)(12). However, in in vitro studies, metformin does inhibit the proliferation and viability of BTC and promote the apoptosis of BTC through various mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Such metabolic alterations not only promote the growth and invasion of tumor cells but also support their chemoresistance [11]. Kaewpitoon et al suggested that metformin might influence tumorigenesis, both indirectly, through the systemic reduction of insulin levels, and directly, via the induction of energetic stress [12]. A recent epidemiologic survey indicated that metformin use was associated with reduced tumor incidence in patients with type II diabetes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent epidemiologic survey indicated that metformin use was associated with reduced tumor incidence in patients with type II diabetes [13][14][15][16]. The anticarcinogenic activity of metformin has been attributed to many mechanisms, including the activation of the liver kinase B1 (LKB1)/AMP-activated protein kinase (AMPK) pathway, inhibition of the unfolded protein response, inhibition of protein synthesis, induction of cell cycle arrest and/or apoptosis, activation of the immune system, and potential eradication of cancer stem cells [12,15,17]. LKB1/AMPK pathway activation inhibits the mammalian target of rapamycin (mTOR), which negatively affects protein synthesis in tumor cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, although Metformin may reduce cancer risk, an effect on survival of CCA patients was not yet demonstrated 20 . These clinical observations were corroborated by basic studies where the potential anti-cancer effect of Metformin has been investigated in different cancer cells [21][22][23] . These studies suggested that Metformin could act via the AMPK/mTORC1 pathway and induce the cell cycle arrest 24 .…”
mentioning
confidence: 72%